Use of Knowledge System in the Rural Community in Improving Livelihood Status of the Farmers under RDRS - Islam, MS; Uddin, ME; Rashid, MU (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The study was focused to determine the extent of use of knowledge system in improving livelihood status of the farmers. The relationship between selected characteristics of the farmers and extent of use of knowledge system in improving their livelihood status was also explored. The study was conducted in Raipur Union of Thakurgaon Sadar Upazila under Thakurgaon District. The population of the study was 146 and seventy percent of the population was selected at random and as such 101 farmers were selected as sample. Data were collected through interview schedule by the researcher himself during 07 February to 28 March 2004. The majority (69 percent) of the respondents possessed medium extent of knowledge while 17 percent low and 14 percent possessed high extent of knowledge on livelihood. Out of thirteen selected characteristics of the respondents level of literacy, farm size, and annual income, farming and living expenditure, innovativeness, communication exposure, cosmopoliteness, organizational participation, aspiration and fatalism had positive significant relationship with the extent of use of knowledge system in improving livelihood status. Key words: Information system, livelihood status, farmers. DOI = 10.3329/jard.v5i1.1474 J Agric Rural Dev 5(1&2), 167-172, June 2007